Functional capacity in adults with hypertension as assessed by the six-minute walk distance test: systematic review - Rodrigo de Assis Ramos; Arthur de Sá Ferreira (Universidade de São Paulo, 2014)
This study systematically reviewed the six-minute walk test (6MWT) for assessment of functional capacity of adults with hypertension subjected or not to physical rehabilitation, focusing in walked distance (6MWD) and blood pressure. A literature search was conducted in PubMed, SciELO, LILACS, PEDro, Cochrane, Redalyc, and national journals of physiotherapy using the keywords "hipertensão" (hypertension) and "teste de caminhada de seis minutos" (six-minute walk test) without language or period constraints. Six studies were included: one case-control, one clinical trial, two quasi-experimental and two series of cases. Results from cross-sectional studies suggest preservation of the 6MWD in the mild stage of hypertension, whereas significant lower values in the more severe stage of hypertension or in the presence of comorbidities. Longitudinal studies suggest that the 6MWT is sensitive to the increase in functional capacity due to adaptations from physical rehabilitation programs. Two major limitations compromise the external validity of the included studies: samples with specific phenotypes (same sex; same hypertension stage; narrow age group) and the small sample size (range 8 to 32). The low methodological quality reinforces the need for researches with larger samples and different phenotypes of hypertension.